Public Value of Using Light Rail Transit Transportation at Palembang - Rattu Nadra Syakila; Sri Suwitri; Tri Yuniningsih (Unit Publikasi Ilmiah, P3M, Politeknik Negeri Bali, 2024)
This study examines the public value derived from the use of the Light Rail Transit (LRT) system in Palembang City and investigates the factors contributing to its formation. Employing a descriptive qualitative approach, data were collected through interviews, observations, and text analysis. Findings reveal that the South Sumatra LRT operates on a well-organized schedule, ensuring seamless travel from Airport Station to DJKA Station and vice versa, without scheduling conflicts. The system also prioritizes passenger comfort through the presence of Crew on Trip Cleaning (OTC) officers responsible for maintaining cleanliness. Additionally, the LRT meets public expectations by offering a suitable route network, planning fleet capacity effectively, establishing consistent departure times, and ensuring high security across its operations. In conclusion, the Palembang LRT system enhances travel comfort with regular scheduling and adequate facilities, highlighting its potential as a key component of Palembang's sustainable urban transportation infrastructure with continued development.